Existence of Banking Credit Agreement with Standard Clauses Related to the Implementation of Consumer Law Protection in Indonesia - Fiver, Ramjahif Pahisa Gorya; Yuhelson, Yuhelson; Prasetyo, Dedy Ardian (Jurnal Indonesia Sosial Sains, 2024)
This study examines the existence of banking credit agreements with standard clauses in the context of the implementation of consumer law protection in Indonesia. Standard clauses are often used by banks to regulate the legal relationship between banks and customers. However, the use of this clause often causes problems because it is considered detrimental to consumers. An agreement made by debtors and creditors is a complex series of laws, the emergence of conditions in an agreement that is still standard made unilaterally by business actors in this case, is banking where consumers have to submit and comply with the agreement there are standards clauses contained in a contract in the future making the consumer's position disadvantaged so that The situation possessed by debtors and creditors or business actors and consumers is not equal. This legal situation makes consumer protection law take many roles against violations or unlawful acts committed by debtors or, in this case, business actors. Legal protection for consumers in Indonesia is regulated in Law Number 8 of 1999 concerning Consumer Protection and Renewal in Law Number 4 of 2023. This study aims to analyze the extent to which standard clauses in banking credit agreements affect consumer rights and how the implementation of consumer law protection in Indonesia. The research method used is juridical normative with a qualitative approach. The results showed that although standard clauses aim for efficiency, they often contain unbalanced provisions that harm consumers. Therefore, tighter supervision and clear regulation are needed to ensure better consumer legal protection in banking credit agreements.